Digital marketing increases competitiveness of msmes in the city of Gorontalo - Rahman, Silviani; Mardiana, Andi (International Journal of Applied Finance and Business Studies, 2024)
The significant increase in the use of digital technology, especially through digital marketing strategies, has become a major catalyst in changing the global business landscape. This research aims to investigate how Micro, Small and Medium Enterprises (MSMEs) in Gorontalo City can utilize digital marketing to increase their competitiveness. By understanding the challenges and opportunities faced by MSMEs at the local level, this research uses scientific study methods with a qualitative metasynthesis approach. The research results show that the use of digital marketing has a positive impact on MSMEs in Gorontalo City. Online marketing strategies, such as promotions through social media and online buying and selling platforms, not only increase product sales but also expand product visibility and fame. Even though there are obstacles such as intense online competition and a lack of understanding of MSME players about digital marketing, outreach, training and mentoring activities have succeeded in increasing their understanding and skills.